Review: Integrated Scientific Literacy on Natural Science Learning - Nainggolan, Ninda Yera Setyo; Sumarni, Woro; Sutikno, Sutikno; lnuwih, Suharto; Wiyanto, Wiyanto (Universitas Negeri Malang, 2021)
This literature review reveals the journal publication on integrated scientific literacy in natural science learning. A systematic review was carried out through a modified and adopted items selected for the systematic review and meta-analysis (PRISMA). The articles with integrated scientific literacy have been detected in a number of journals, such as ERIC, SCIENCE DIRECT, IJSE, SE, JRST, IOP SCIENCE, DOAJ, and Springer, using the keywords of